Construction of a lncRNA–mRNA Co-Expression Network for Nasopharyngeal Carcinoma - Fan, Chunmei; Xiong, Fang; Tang, Yanyan; Li, Panchun; Zhu, Kunjie; Mo, Yongzhen; Wang, Yumin; Zhang, Shanshan; Gong, Zhaojiang; Liao, Qianjin; Li, Guiyuan; Zeng, Zhaoyang; et al. (Frontiers in Oncology, 2022)
Long non-coding RNAs (lncRNAs) widely regulate gene expression and play important roles in the pathogenesis of human diseases, including malignant tumors. However, the functions of most lncRNAs remain to be elucidated. In order to study and screen novel lncRNAs with important functions in the carcinogenesis of nasopharyngeal carcinoma (NPC), we constructed a lncRNA expression profile of 10 NPC tissues and 6 controls through a gene microarray. We identified 1,276 lncRNAs, of which most are unknown, with different expression levels in the healthy and NPC tissues. In order to shed light on the functions of these unknown lncRNAs, we first constructed a co-expression network of lncRNAs and mRNAs using bioinformatics and systematic biological approach. Moreover, mRNAs were clustered and enriched by their biological functions, and those lncRNAs have similar expression trends with mRNAs were defined as functional molecules with potential biological significance. The module may help identify key lncRNAs in the carcinogenesis of NPC and provide clues for in-depth study of their functions and associated signaling pathways. We suggest the newly identified lncRNAs may have clinic value as biomarkers and therapeutic targets for NPC diagnosis and treatment.